2015
DOI: 10.3109/23744235.2015.1107188
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in the gene encoding macrophage migration inhibitory factor (MIF) are associated with active pulmonary tuberculosis

Abstract: These data suggested a distinct genetic and immunopathogenic basis for tuberculosis at the MIF locus. Serum MIF, IFN-γ and TNF-α profiles distinguish tuberculosis from the more inflammatory phenotype and may play a role in pathogenesis and as biomarkers of active tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The data reported that the MIF −173*C allele was significantly more common in pulmonary TB cases than it was in healthy controls ( p = .02, OR = 1.53, 95% CI 1.05–2.24). The same results were shown for different degrees of TB risk in Chinese population (Kuai et al., ; Li et al., ; Liu et al., ; Wang, Zhang, Shi, Zhang, & Liu, ) and, more recently, in Iranian populations ( p = .028) (Hashemi et al., ), in which the −173*C allele was found to be associated with susceptibility to TB. This mutation occurred in an interesting region of the MIF promoter.…”
Section: Candidate Genes and The Risk Of Developing Tbsupporting
confidence: 68%
See 2 more Smart Citations
“…The data reported that the MIF −173*C allele was significantly more common in pulmonary TB cases than it was in healthy controls ( p = .02, OR = 1.53, 95% CI 1.05–2.24). The same results were shown for different degrees of TB risk in Chinese population (Kuai et al., ; Li et al., ; Liu et al., ; Wang, Zhang, Shi, Zhang, & Liu, ) and, more recently, in Iranian populations ( p = .028) (Hashemi et al., ), in which the −173*C allele was found to be associated with susceptibility to TB. This mutation occurred in an interesting region of the MIF promoter.…”
Section: Candidate Genes and The Risk Of Developing Tbsupporting
confidence: 68%
“…Another genetic variant, a −794 (rs5844572) CATT 5–8 microsatellite not yet investigated in Moroccan population, was identified to be associated with TB in Chinese population (Kuai et al., ; Li et al., ; Tong et al., ; Wang et al., ).…”
Section: Candidate Genes and The Risk Of Developing Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms of MIF in the promoter region were identified by SNP MIF‐173(G/C) and MIF‐794 CATT. It was reported in inflammatory diseases that carriers of MIF‐173 C and MIF‐794 CATT 7 or 8 alleles were susceptible to active tuberculosis with MIF in serum significantly increasing . The mechanism might be that MIF polymorphisms are associated with susceptibility to active tuberculosis, and MIF levels in serum may contribute to disease persistence by inducing interferon‐γ and tumor necrosis factor‐α to promote inflammatory responses by means of positive feedback loop .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in inflammatory diseases that carriers of MIF‐173 C and MIF‐794 CATT 7 or 8 alleles were susceptible to active tuberculosis with MIF in serum significantly increasing . The mechanism might be that MIF polymorphisms are associated with susceptibility to active tuberculosis, and MIF levels in serum may contribute to disease persistence by inducing interferon‐γ and tumor necrosis factor‐α to promote inflammatory responses by means of positive feedback loop . It is also reported that polymorphisms of MIF‐173(G/C) and MIF‐794 CATT play important roles in prostatic cancer and gastric cancer .…”
Section: Introductionmentioning
confidence: 99%